The Effect of Financial Management Practices on the Financial Performance of Small and Medium Enterprises in Mukono Municipality - Immaculate A. Nabasa (Uganda Christian University, 2025)
The purpose of the study was to examine the Effect of Financial Management Practices on the Financial Performance of Small and Medium Enterprises (SMEs) in Mukono Municipality. Particularly, it took into account the research on the relationship between budgeting practices and the financial performances of SMEs, establishing working capital management as a determinant of financial performance of SMEs, and ascertaining the relationship between financial record keeping and the financial performance of SMEs in Mukono Municipality. Furthermore, the study was conducted using a cross-sectional survey research design where quantitative research approach was also employed. A sample size of 80 SMEs operating in Kauga, Mukono Municipality was selected using simple random sampling method. Data was collected using questionnaires and later analyzed using SPSS. All the ethical considerations while collecting data were fully considered by the researcher. The study findings established that budgeting practices (r = .875**, p < .05), working capital management (r = .883**, p < .05), and financial record keeping (r = .879**, p < .05) each have a strong positive and significant influence on the financial performance of SMEs in Mukono Municipality, with effective budgeting improving planning, decision-making, and resource optimization, proper working capital management ensuring liquidity, efficiency, and supplier relations, and accurate financial records enhancing accountability, decision-making, and access to credit. Finally, the study recommended that SMEs in Mukono Municipality prioritize effective budgeting, efficient working capital management, and accurate financial record keeping, supported by staff training and the adoption of technological financial management tools, to enhance planning, liquidity, accountability, decision-making, and overall financial performance, thereby promoting growth, sustainability, and competitiveness.
Undergraduate Thesis